Defining and characterising a toolkit for the development of a successful European registry for rare liver diseases: a model for building a rare disease registry. Issue 4 (2022) - Pericleous, Marinos; Kelly, Claire; Schilsky, Michael; Dhawan, Anil; Ala, Aftab
No abstract available